The Eastern Mediterranean as a focus for the EU's energy transition: Deep-rooted enmities and new opportunities for cooperation between Greece, Turkey and Cyprus - Moritz Rau; Günter Seufert; Kirsten Westphal (Stiftung Wissenschaft und Politik (SWP), 2022)
The EU and Germany have set themselves ambitious climate and energy policy targets. Taking into account the need to reduce emissions from all sectors of the economy, they now have a different perspective on the energy situation in the Eastern Mediterranean than a few years ago.
Keywords: 330